The Influence of Entrepreneurial Orientation on Cultural Institution’s Performance: An Empirical Study on 74 Public Cultural Institutions in Poland - Anna SCHNEIDER-LUKOWCZYK (Communications of International Proceedings, 2024)
The existing literature on the relationship between entrepreneurial orientation and performance has mainly focused on business organizations. Despite the growing interest in entrepreneurial orientation in the non-profit sector, the field remains fragmented in cultural institutions. This research addresses the gap in the literature by assessing the impact of entrepreneurial orientation dimensions – innovativeness, proactiveness, and risk-taking – on social and economic performance in the context of cultural institutions. A model of the relationships was developed based on an extensive literature review and empirically tested using survey data collected from 74 public theatres and music institutions based in Poland. The data were analyzed using structural equation modeling. The empirical analysis reveals that proactiveness is the most crucial entrepreneurial dimension for both the social and economic performance of theatres and music institutions. Moreover, the findings indicate that while innovativeness does not enhance performance, there is a significant correlation between risk-taking and economic performance. Furthermore, the study discusses the practical implications, limitations, and future directions.
Keywords: Entrepreneurial Orientation; Performance; Cultural Institution; Non-Profit Organization